Detection of G Protein‐Coupled Receptor Complexes in Postmortem Human Brain by Proximity Ligation Assay. Issue 1 (13th January 2020) - Zhu, Ying; Dwork, Andrew J.; Trifilieff, Pierre; Javitch, Jonathan A.
Abstract: Combining immunological and molecular biological methods, the antibody‐based proximity ligation assay (PLA) has been used for more than a decade to detect and quantify protein‐protein interactions, protein modification, and protein expression in situ, including in brain tissue. However, the transfer of this technology to human brain samples requires a number of precautions due to the nature of the specimens and their specific processing. Here, we used the PLA brightfield detection technique to assess the expression of dopamine D2 receptor and adenosine A2A receptor and their proximity in human postmortem brains, and we developed a systematic random sampling method to help quantify the PLA signals. © 2019 by John Wiley & Sons, Inc. Basic Protocol 1 : Sample preparation and sectioning for PLA_BF Basic Protocol 2 : PLA_BF staining of brain tissue Basic Protocol 3 : Image acquisition and result analysis Support Protocol : Luxol fast blue/cresyl violet staining